Introduction to the Special Issue: Contemporary Irish Television. (January 2021) - Free, Marcus
This special issue examines aspects of Irish television at the current political, economic and cultural conjuncture in Ireland, and against the backdrop of two major crises since the 1990s: the first deriving from the Catholic Church's institutional abuse scandals, which progressively weakened its power and influence; the second from the 2008 collapse of the Celtic Tiger economic boom, following which years of austerity have deepened social inequality. Focusing primarily on Ireland's public service broadcaster RTÉ, the articles consider how national television in Ireland has represented and negotiated the resultant tensions and divides within Irish society. They examine the endurance and evolution of a daily Catholic ritual on national television; the weaknesses of a transnational drama in addressing the legacy of institutional abuse; varieties of progressive post-2015 Marriage Equality referendum "queer" television; "property television" and the current housing crisis; and intergenerationally themed reality television in the context of growing generational inequality.